On the economics of crisis contracts - Elias Aptus; Volker Britz; Hans Gersbach (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We examine the impact of so-called Crisis Contracts on bank managers' risktaking incentives and on the probability of banking crises. Under a Crisis Contract, managers are required to contribute a pre-specified share of their past earnings to finance public rescue funds when a crisis occurs. This can be viewed as a retroactive tax that is levied only when a crisis occurs and that leads to a form of collective liability for bank managers. We develop a game-theoretic model of a banking sector whose shareholders have limited liability, so that society at large will suffer losses if a crisis occurs. Without Crisis Contracts, the managers' and shareholders' interests are aligned, and managers take more than the socially optimal level of risk. We investigate how the introduction of Crisis Contracts changes the equilibrium level of risk-taking and the remuneration of bank managers. We establish conditions under which the introduction of Crisis Contracts will reduce the probability of a banking crisis and improve social welfare. We explore how Crisis Contracts and capital requirements can supplement each other and we show that the efficacy of Crisis Contracts is not undermined by attempts to hedge.
Keywords: C79; G21; G28; 330; banking crises; Crisis Contracts; excessive risk taking; banker's pay; hedging; capital requirements